Sosialisasi Membuat Desain Menggunakan Aplikasi Canva di Kelurahan Sukorame - Sukmana, Kevin Ramadhany; Prabowo, Budi; Hidayat N, Rusdi; Dwiridhotjahjono, Jojok (Jurnal Bisnis Indonesia, 2024)
This research aims to conduct outreach regarding the use of the Canva application as an effectivedesign tool for Micro, Small and Medium Enterprises (MSMEs/UMKM). Attractive visual design hasan important role in promoting UMKM products or services in the current digital era. However,limited knowledge and access to design tools often become obstacles for Sukorame UMKM. Themethod used in this research is a training and socialization approach. An intensive training programon using the Canva application will be held for Sukorame UMKM owners and related staff. Inaddition, individual discussion and guidance sessions will be held to understand the needs and designchallenges faced by each UMKM resident of Sukorame. It is hoped that the results of this researchwill provide a better understanding of the capabilities and benefits of the Canva application indesigning promotional materials. Apart from that, it is also hoped that it can improve the design skillsof UMKM owners and related staff, so that they can produce promotional materials that are moreeffective and attractive to their market. Through this socialization, it is hoped that Sukorame UMKMcan be more competitive in digital marketing and have the ability to present their products or servicesin a more attractive and professional way. In this way, it is hoped that it can also contribute toincreasing the competitiveness of UMKM in today's increasingly competitive business ecosystem.Keywords: Socialization; Canva; MSMEs; Design